Longitudinal Study of Cognitive and Emotional Alterations in Amyotrophic Lateral Sclerosis: Clinical and Imaging Data - Benbrika, Soumia; Doidy, Franck; Carluer, Laurence; Mondou, Audrey; Pélerin, Alice; Eustache, Francis; Viader, Fausto; Desgranges, Béatrice (Frontiers in Neurology, 2021)
Objectives: Extra-motor manifestations occur in 50% of patients with amyotrophic lateral sclerosis (ALS). These mainly concern cognition and behaviour. Depression and anxiety are less frequent. Little is known about how these manifestations change as the disease progresses. Similarly, although cortical thinning has been well documented at disease onset, there are scant data about cortical thinning over time and how this correlates with extra-motor manifestations. The present study therefore assessed cognitive, emotional and psychological state and cortical thinning in a group of patients with ALS at baseline and after a follow-up period. Methods: We assessed executive functions, facial emotion recognition, depressive and anxious symptoms, and cortical thinning in 43 patients with ALS at baseline, comparing them with 28 healthy controls, and 21 of them 9 months later. We looked for links among the extra-motor manifestations and correlations with cortical thickness. Results: At baseline, patients had poor executive function and recognition of complex emotions from the eyes, and more anxious and depressive symptoms than controls. At follow-up, only inhibition abilities had worsened. Cortical thinning was observed in bilateral precentral regions and other parts of the cerebral cortex at baseline. Over time, it worsened in motor and extra-motor areas. Executive functions correlated with thinning in the middle and inferior frontal gyrus and orbitofrontal cortex. Conclusions: During follow-up, there was little deterioration in extra-motor manifestations and psychological state, despite continuing cortical thinning. Patients with affective ToM changes seemed less depressed than the others. Impaired mental flexibility was subtended by prefrontal regions with cortical thinning.